Construction of gradient layered structure for microwave absorbing composite materials with strong absorption and high bandwidth - Mei Guo; Zikang Han; Guangsheng Shi; Rong Chen; Jiang Li; Shaoyun Guo (Polymer Testing)
The unique properties of two-dimensional metal carbides (MXene) make them promising for use in absorbing electromagnetic waves. However, their high conductivity and single dielectric loss mechanism lead to poor impedance matching, and limit their performance in absorbing microwaves. In this paper, a gradient layered structure using MXene combined with waterborne polyurethane (WPU) was designed, and MXene content or nickel content after the magnetization treatment of MXene were varied to create gradient changes in the electromagnetic parameters. It was shown that designing gradient layered structures with different characteristic impedances can allow more electromagnetic waves to enter the substrate and undergo multiple reflections and dissipation at the inner layer and interface. Through optimal structural design, the multi-layer sample (NM11-10)1(NM11-25)2 achieved an effective absorption bandwidth of 6.80 GHz at a thickness of 4.0 mm, which is 66 % higher than the absorption bandwidth of the corresponding single-layer sample NM11-10 (4.10 GHz). This method provides a preparation process for flexible, lightweight, and broadband absorbing materials, showing significant promise for the application of MXene composite materials in the field of wave absorption.